Genetic determinants and stroke in children with sickle cell disease - Daniela O.W. Rodrigues; Luiz C. Ribeiro; Lysla C. Sudário; Maria T.B. Teixeira; Marina L. Martins; Anuska M.O.L. Pittella; Irtis de O. Fernandes Junior (Brazilian Society of Pediatrics, 2016)
Objective: To verify genetic determinants associated with stroke in children with sickle cell disease (SCD). Methods: Prospective cohort with 110 children submitted to neonatal screening by the Neonatal Screening Program, between 1998 and 2007, with SCD diagnosis, followed at a regional reference public service for hemoglobinopathies. The analyzed variables were type of hemoglobinopathy, gender, coexistence with alpha thalassemia (α‐thal), haplotypes of the beta globin chain cluster, and stroke. The final analysis was conducted with 66 children with sickle cell anemia (SCA), using the chi‐squared test in the program SPSS® version 14.0. Results: Among children with SCD, 60% had SCA. The prevalence of coexistence with α‐thal was 30.3% and the Bantu haplotype (CAR) was identified in 89.2%. The incidence of stroke was significantly higher in those with SCA (27.3% vs. 2.3%; p = 0.001) and males (24.1% vs. 9.6%; p = 0.044). The presence of α‐thal (p = 0.196), the CAR haplotype (p = 0.543), and socioeconomic factors were not statistically significant in association with the occurrence of stroke. Conclusion: There is a high incidence of stroke in male children and in children with SCA. Coexistence with α‐thal and haplotypes of the beta globin chain cluster did not show any significant association with stroke. The heterogeneity between previously evaluated populations, the non‐reproducibility between studies, and the need to identify factors associated with stroke in patients with SCA indicate the necessity of conducting further research to demonstrate the relevance of genetic factors in stroke related to SCD.